Damıtılmış Temsiller: Anadolu’da Kült Kontekstinde Bulunan Minyatür Kaplar Üzerine / Distilled Representations: On Miniature Vessels Found in Cult Context in Anatolia - Esen KAYA (Arkhaia Anatolika, 2020)
The miniature objects, the subjects of increasing research interest in recent years, are a group of finds frequently encountered in the domestic, funerary and cultic settings. The ongoing efforts to develop definitions and terminology alongside with the analytical attempts to discover the mindset behind miniaturization have had an impact in our attempt of perception of the nature of these objects. The miniature vessels stand as the expressions of miniaturization frequently -and often in large quantities- discovered in religious contexts. These vessels, the formerly assumed economic representations of their full-sized counterparts, are currently considered as the objects manipulating reality in line with the emotions. This study aims to provide an overview of the research in the field through a survey of the selected examples where miniature vessels were recorded in religious context in Anatolia. The first part of the study gathers the analyses on the phenomenon of miniaturization and the miniatures with a special focus on the representation of miniature vessels in the cult context, providing the inferences of the setting, arrangement, functionality, quantity, emotion, and the role of these objects in ritual. The second part of the study presents the examples displaying certain patterns among the centres where miniature vessels were found in the cult context in Anatolia. The miniature vessels have often been unearthed en masse in the deposits rather than in their original settings, which makes it difficult to interpret these objects evaluated based on the assumption that they gain meaning according to the context. However, some exceptional in situ contexts besides reflecting the religious arrangement of miniature vessels may also effectively identify the sacred space and/or define ritual and reach inferences of human behaviour. There are cases where these groups of finds were uncovered in already identified sacred spaces, whereas there are also some that these miniature vessels attribute “sacredness” to the spaces where they were found based on the vessel form, the assemblage and the setting.